Readiness of Electronic Medical Record Implementation at Budi Asih Trenggalek Hospital Using the Fishbone Diagram Method - Chery Putria Santoso; Ani Rosita (Garuda Pelamonia Jurnal Keperawatan, 2025)
Electronic Medical Records (EMR) are an important component in supporting the digital transformation of healthcare services, aiming to improve the effectiveness, efficiency, and accuracy of patient medical data management in hospitals. This study aims to determine the readiness of EMR implementation at Budi Asih Hospital Trenggalek using the Fishbone Diagram method as an analytical tool to identify factors influencing implementation readiness. This research employed a descriptive method with a qualitative approach to explore the EMR implementation process comprehensively. Data were collected through in-depth interviews and direct observations involving 20 informants who actively used the EMR system in their daily activities. The results showed that EMR implementation readiness at Budi Asih Hospital was influenced by five main factors: man (human resources), material (tools), machine (data), method (procedures), and money (budget). Healthcare workers and administrative staff were able to operate the EMR system effectively, supported by regular training and workshops. Supporting equipment and systems were available and maintained periodically to ensure stability. Data management was conducted accurately and timely through routine audits to maintain data quality. The hospital also had clear Standard Operating Procedures (SOPs) and budget allocation to support EMR sustainability. Overall, Budi Asih Hospital demonstrated good readiness in implementing EMR and is prepared to further develop the system to improve healthcare service quality.